Formation of Organizational Forms of Internal Control and Audit - Nino Pailodze; Rusudan Kutateladze; Tornike Dzagnidze (Journal of Management Practices, Humanities and Social Sciences, 2020)
The purpose of this research paper is to improve the processes of designing, implementing, and applying audit methods and procedures within the corporate governance system, to clarify and formulate a single and understandable apparatus of “corporate governance”, which will allow us to determine the place and role of internal audit in the corporate governance system. The paper uses a complex methodology for studying the topic, including methods such as analysis and synthesis, comparison, and statistical assessment. Key findings of current study are a system of quantitative and qualitative indicators that expresses the economic interests and control parameters of a group of corporate governance entities. It will help to evaluate the level of performance of the analytical facility using the paired comparison method. Relevance of the topic is related to the fact that the creation and development of internal audit function are connected to the creation and development of joint-stock companies caused by post-soviet privatization of property in Georgia. There is a substantial volume of research that gives a general perspective about the internal audit of corporate governance, but the creation of the conceptual model of internal audit in the corporate governance system and its auditory assessment methods remain the least scrutinized field of economic science.